Determination of Sildenafil in herbal aphrodisiac products available in local market by TLC and HPLC - بركات هلا; اسكيف سيمون (Latakia University Journal -Medical Sciences Series, 2021)
The study aims to detect sildenafil in some herbal aphrodisiac products available in Syrian market from different sources. Therefore, we studied 10 samples of herbal aphrodisiac preparations available in Syrian market. packaging and labelling test applied to all samples, then, these samples were analyzed chromatographically to detect sildenafil. Samples were examined using TLC methanol/ethyl acetate (2: 1). Then, HPLC analysis was conducted, using a column (C18, 10 µm, 125 * 4 mm), mobile phase: methanol/water (35:65), flow: 1.5 ml/min, UV detection: 240 nm. Packaging test revealed that all of the locally manufactured samples matching to WHO guidelines, while the illegal sample and one of the imported samples violated the recommendations. The chromatographic analysis confirmed the presence of Sildenafil in one of the tested samples, with an amount of (12.754) mg/capsule.